![image](//tex.z-dn.net/?f=%5Cfrac%7B3%7D%7Bx%5E%7B2%7D-2x-2%20%7D%20-x%5E%7B2%7D%2B2x%3D0)
![image](//tex.z-dn.net/?f=%5Cfrac%7B3%7D%7Bx%5E%7B2%7D-2x-2%20%7D%20-(x%5E%7B2%7D-2x)%3D0)
Пусть х²-2х = t, тогда
_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _
ОДЗ:
t-2≠0
t≠2
_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _
![image](//tex.z-dn.net/?f=%5Cfrac%7B3%7D%7Bt-2%7D%20-t%3D0)
![image](//tex.z-dn.net/?f=%5Cfrac%7B3-t*(t-2)%7D%7Bt-2%7D%3D0)
![image](//tex.z-dn.net/?f=%5Cfrac%7B3-t%5E%7B2%7D%2B2t%7D%7Bt-2%7D%3D0)
| : (-1)
![image](//tex.z-dn.net/?f=%5Cfrac%7Bt%5E%7B2%7D-2t-3%7D%7Bt-2%7D%3D0)
t²-2t-3=0
D = (-2)² - 4*1*(-3) = 4+12 = 16 = 4²
![image](//tex.z-dn.net/?f=t_%7B1%7D%20%3D%5Cfrac%7B2%2B4%7D%7B2*1%7D%3D%20%5Cfrac%7B6%7D%7B2%7D%3D3)
![image](//tex.z-dn.net/?f=t_%7B2%7D%20%3D%5Cfrac%7B2-4%7D%7B2*1%7D%3D%20-%5Cfrac%7B2%7D%7B2%7D%3D-1)
Вернёмся к замене:
![image](//tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%5E%7B2%7D-2x%3D3%5C%5Cx%5E%7B2%7D-2x%3D-1%5C%5C%5Cend%7Barray%7D)
![image](//tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%5E%7B2%7D-2x-3%3D0%5C%5Cx%5E%7B2%7D-2x%2B1%3D0%5C%5C%5Cend%7Barray%7D)
х²-2х-3=0
D = (-2)² - 4*1*(-3) = 4+12 = 16 = 4²
![image](//tex.z-dn.net/?f=x_%7B1%7D%20%3D%5Cfrac%7B2%2B4%7D%7B2*1%7D%3D%20%5Cfrac%7B6%7D%7B2%7D%3D3)
![image](//tex.z-dn.net/?f=x_%7B2%7D%20%3D%5Cfrac%7B2-4%7D%7B2*1%7D%3D%20-%5Cfrac%7B2%7D%7B2%7D%3D-1)
х²-2х+1=0
D = (-2)² - 4*1*1 = 4-4 = 0
![image](//tex.z-dn.net/?f=x_%7B3%7D%20%3D%20%5Cfrac%7B2%7D%7B2*1%7D%3D1)
Ответ: х₁=-1, х₂=1, х₃=3